Obstructive sleep apnea in community-dwelling polio survivors: a 5-year longitudinal follow-up study - Ding, Qidi; Li, Xiao; Wang, Meng; Wang, Jingyu; Sun, Ting; Sun, Yunliang; Liu, Jianghua; Yu, Yan; Wu, Jinxian; Du, Juan; Dong, Xiaosong; Zhang, Chi; et al. (Frontiers in Neurology, 2025)
PurposeObstructive sleep apnea (OSA) is highly prevalent in polio survivors, but longitudinal data on its progression remain limited. This study aimed to characterize OSA progression in community-dwelling polio survivors and compare it with an age-matched control group.MethodsA prospective 5-year longitudinal study recruited 148 polio survivors (48.76 ± 5.97 years, 75% male). At baseline (2014), all participants underwent overnight oximetry. Among them, 42 completed in-lab polysomnography (PSG) testing. Over the 5-year follow-up, 112 polio survivors (76.79% male, mean age 48.48 ± 6.05 years) were successfully tracked, with 33 undergoing follow-up PSG. Additionally, 59 age- and sex-matched OSA patients were enrolled as controls. Primary outcomes included changes in oxygen desaturation index ≥4% (ODI4) and apnea-hypopnea index (AHI). Correlates of OSA progression were analyzed using Pearson’s correlations.ResultsOver 5 years, ODI4 increased significantly in polio survivors from 8.11 ± 9.13 to 10.35 ± 11.63 events/h (p = 0.01), with a shift toward moderate–severe ODI4 (13 to 22%, p = 0.027). AHI also rose in both groups: polio survivors (26.57 ± 21.25 to 33.86 ± 22.43 events/h, p = 0.02) and controls (27.14 ± 21.91 to 37.24 ± 24.55 events/h, p = 0.004), with no significant group difference in AHI progression (p = 0.89). However, polio survivors showed increased mixed apnea index (p = 0.02) and prolonged REM sleep latency (p = 0.009). ODI4 changes correlated with scoliosis (r = 0.27, p = 0.005) and BMI fluctuations (r = 0.25, p = 0.008).ConclusionOSA-related parameters, particularly mixed apnea and REM alterations, progress in polio survivors. Changes in ODI4 were positively correlated with BMI fluctuations and scoliosis.